2023
DOI: 10.1186/s13046-022-02589-7
|View full text |Cite
|
Sign up to set email alerts
|

S1PR1/S1PR3-YAP signaling and S1P-ALOX15 signaling contribute to an aggressive behavior in obesity-lymphoma

Abstract: Background Excess body weight has been found to associate with an increased risk of lymphomas and some metabolic pathways are currently recognized in lymphomagenesis. Bioactive lipid metabolites such as sphingosine-1-phosphate (S1P) have been proposed to play an important role linking obesity and lymphomas. However, the underlying mechanism(s) of S1P signaling in obesity-lymphomagenesis have not been well addressed. Methods The gene expression of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…72 PC-3 cells express S1P1, S1P2, and S1P3, 8 all of which can activate YAP. 71,73,74 Thus, it is likely that both LPA and S1P induce CCN proteins via a YAP-dependent pathway in PC-3 cells. We report for the first time, that 18:1-LPA and 18:0 LPA have differential effects on CCN1 induction in prostate cancer cells, with 18:1-LPA being more efficacious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…72 PC-3 cells express S1P1, S1P2, and S1P3, 8 all of which can activate YAP. 71,73,74 Thus, it is likely that both LPA and S1P induce CCN proteins via a YAP-dependent pathway in PC-3 cells. We report for the first time, that 18:1-LPA and 18:0 LPA have differential effects on CCN1 induction in prostate cancer cells, with 18:1-LPA being more efficacious.…”
Section: Discussionmentioning
confidence: 99%
“… 72 PC‐3 cells express S1P1, S1P2, and S1P3, 8 all of which can activate YAP. 71 , 73 , 74 Thus, it is likely that both LPA and S1P induce CCN proteins via a YAP‐dependent pathway in PC‐3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In detailing the mechanism of sphingosine-1-phosphate (S1P) in obesitylymphomagenesis, a recent study demonstrated that up-regulated S1P-S1P receptors 1/2-YAP signaling mediates the aggressive nature of obesity-lymphoma by inducing cell proliferation and migration. More importantly, S1P-ALOX15 signaling mediates polarization of macrophages towards tumor-associated macrophages, establishing an immunosuppressive microenvironment [209]. In a separate study, both ALOX15 and ALOX15B isoforms were identified in normal mammary epithelial cells as well as in vascular endothelial cells, and the expression of both isoforms was considerably diminished in breast tumor tissues [143].…”
Section: Lipoxygenases and Immune Suppression In Tumor Growthmentioning
confidence: 98%
“…Aside from normal cell types, S1PR3 is highly expressed in various cancer cells and was shown to stimulate cancer progression [ 21 , 153 , 168 ]. It is common to observe the co-expression of different S1P receptors, especially presence of S1PR1 and S1PR3 within one cell type which may indicate cooperation of signaling among the receptors [ 174 ]. In comparison to S1PR1 and S1PR3 effects, S1PR4 was found to be growth-inhibitory in some immune cells [ 175 ], while its role in the lymphocyte trafficking and expansion was extensively discussed [ 169 ].…”
Section: Sphingolipids As Mediators Facilitators and Inhibitors Of Tn...mentioning
confidence: 99%